Alcohol use and its association with suicide attempt, suicidal thoughts and non-suicidal self-harm in two successive, nationally representative English household samples. Issue 6 (3rd November 2022) - Ledden, Sarah; Moran, Paul; Osborn, David; Pitman, Alexandra
Abstract : Background: Alcohol use is a risk factor for suicidal behaviour, yet the nature of the relationship is unclear. Most research on the topic is conducted in clinical populations, with few studies exploring this association across the general population. Aims: We investigated the association between specific domains of alcohol use and suicide attempt, suicidal thoughts and non-suicidal self-harm in a general population sample. Method: A total of 14 949 adults who completed the 2007 or 2014 Adult Psychiatric Morbidity Survey were included. We measured alcohol use with the Alcohol Use Disorders Identification Test (AUDIT). Domains of alcohol use relating to risk categories, weekly consumption, binge drinking, dependence symptoms, harmful effects and concern from others were derived from relevant AUDIT items. Self-reported past year suicide attempt, suicidal thoughts and non-suicidal self-harm were measured with the Clinical Interview Schedule, Revised. Results: We found a linear association between total AUDIT score and outcomes. Three of six specific domains of alcohol use (dependence symptoms, harmful effects of drinking and binge drinking) were associated with increased odds of all three outcomes. There was no association of outcomes with the other domains of alcohol use. Conclusions: We found evidence of a linear association between total AUDIT score and suicide attempt, suicidal thoughts and non-suicidal self-harm in a representative English general population sample. Our analyses suggest that where alcohol use significantly disrupts day-to-day functioning, this may underpin the relationship between alcohol use and suicide-related outcomes to a greater extent than higher alcohol consumption. Longitudinal research is needed to further understand these relationships.